National Jail Census, 1993 ([Verlag nicht ermittelbar], 1996)
This data collection is part of a series of data collection efforts aimed at studying the nation's locally administered jails. The 1993 census included all locally administered confinement facilities (3,287) that held inmates beyond arraignment and were staffed by municipal or county employees. The census also included 17 jails that were privately operated under contract for local governments and seven facilities maintained by the Federal Bureau of Prisons and functioning as jails. For purposes of this data collection, a local jail was defined as a confinement facility intended for holding adults, and in some cases juveniles pending adjudication or having sentences of a year or less. Jails were further defined as being administered by a local law enforcement agency. Variables include information on jail population by legal status, age, and sex of prisoners, maximum sentence, admissions and releases, available services and programs, structure and capacity, facility age and use of space, expenditure, employment, staff information, and health issues, which include statistics on drugs, AIDS, and tuberculosis.